19 "Love The Day Job Still;" "More Job Satisfaction;" "I Will Never Give Up My GeriGP Job;" - Results of the BGS GeriGP Workforce Survey 2018. (6th February 2020) - Davies, K; Kalmus, E; Keeble, M; Lawn, L
Abstract: Background: In 2017, two GPs decided to form the GeriGP group, for BGS GP members with a particular interest in the care of older people. GPs are increasingly using their holistic approach and expertise in new models of care within the community and the acute setting ("GeriGP" roles), and many no longer work in traditional General Practice. Introduction: By late 2018, the group had around 100 members. The committee recognised the vital role GeriGPs could play in the development and delivery of innovative models of care for older people, as recommended in the NHS Long Term Plan 1 and 2019 GP Contract 2 . There was no data available about GeriGP roles, which appeared to have arisen in an ad hoc fashion. An online survey was undertaken with the aim of using the results to engage with national policy makers and to identify pathways into these roles to improve recruitment and retention of the GP workforce. 3 Methods: We are grateful to the BGS who collated 58 questions for the online questionnaire, which was sent to all GeriGP members between October and December 2018. There were five main categories: role and venue; employment conditions; indemnity; appraisal; qualifications and training. Most questions had space for free-text comments. Results: 47/100 GeriGP members responded; 68% respondents held GeriGP roles of whom 62% were practising GPs. 60% of all respondents were over 45 years old. 30 job descriptions covered community frailty hubs, intermediate care, community hospitals, care homes, acute front door, visiting services and memory clinics. 60% were community based. Rates of pay and types of contract varied dramatically. GP appraisal was often difficult due to patients having frailty or dementia, with contradictory advice common. 45% had difficulty accessing training and two-thirds of jobs were gained by word-of-mouth. 87% in GeriGP roles were more likely to continue practicing medicine because of this role, yet career development barriers existed at all levels. Many comments concurred with a plea for a ``primary care geriatrics specialty'', and repeatedly the joy of having time for patient-centred care was the driving force behind experienced GPs opting to continue in GeriGP roles. Conclusions: The enthusiasm for GeriGP roles should be seized upon to improve healthcare of older people and bolster the GP workforce. GeriGPs plan to use these results to influence policy makers nationally. References: 1. NHS Long Term Plan (https://www.longtermplan.nhs.uk/online-version/overview-and-summary ). 2. 2019 GP Contract (https://www.england.nhs.uk/wp-content/uploads/2019/01/gp-contract-2019.pdf ). 3. GeriGPs. (https://www.bgs.org.uk/gerigps ).